108PTargeted proximity ligation assays combined with sequencing for robust detection of translocations in FFPE samples. (7th November 2019) - Feitsma, H; Yilmaz, M; Swennenhuis, J; Rakszewska, A; Hajo, K; Splinter, E; Simonis, M; Van Min, M; Van Wezel, T
Abstract: Background: Structural variants in DNA such as translocations are increasingly found as key oncogenic events in tumors, and detection is clinically relevant for therapy choice in many conditions. Despite developments in targeted and whole genome gene sequencing, the robust detection of structural variants remains a challenge, especially in FFPE specimens. Methods: Targeted proximity ligation assays selectively amplify and sequence entire genes based on the crosslinking of physically proximal sequences, and thereby enable complete sequencing of genes of interest, including single nucleotide and structural variants. Because these assays are based on the crosslinking and fragmenting of DNA, they have particular advantages in the analysis of FFPE samples, in which DNA is inherently crosslinked and fragmented. Results: We will show that we have successfully developed targeted proximity ligation assays on representative clinical FFPE samples with considerably fragmented DNA. By making use of the DNA crosslinks in these samples, we can generate very broad sequence information over 100's of kb's, where other targeted NGS technologies are limited by the fragment size. We will show that we can detect NTRK fusions at DNA level, including determination of the fusion partner and the exact translocation breakpoint sequence. The latter can be used as a very sensitive and cancer-specific marker for minimal residual disease (MRD) testing and ctDNA monitoring with PCR. Conclusions: Our newly developed targeted proximity ligation assays enable robust detection of structural variation in FFPE samples and the development of personalized MRD/ctDNA tests. Legal entity responsible for the study: Cergentis. Funding: Cergentis via Horizon2020 SME funding. Disclosure: H. Feitsma: Full / Part-time employment: Cergentis. M. Yilmaz: Full / Part-time employment: Cergentis. J. Swennenhuis: Full / Part-time employment: Cergentis. A. Rakszewska: Full / Part-time employment: Cergentis. K. Hajo: Full / Part-time employment: Cergentis. E. Splinter: Full / Part-time employment: Cergentis. M. Simonis: Full / Part-time employment: Cergentis. M. Van Min: Shareholder / Stockholder / Stock options, Full / Part-time employment: Cergentis. All other authors have declared no conflicts of interest.